Pengaruh Money Politics Terhadap Pilihan Masyarakat Pada Pilkades Serentak di Kabupaten Muara Enim Tahun 2017 (Studi Kasus di Desa Teluk Limau Kecamatan Gelumbang) - Kazali, Revi; Rochmiatun, Endang; Adytyas, Nico Oktario (Program Studi Politik Islam Universitas Islam Negeri Raden Fatah Palembang, 2020)
The paper is “Titled the effect of money politics on community choice in the simultaneous Pilkades in Muara Enim distric in 2017 ( Case studi in the village of Teluk Limau, Gelumbang district)”. The purpose of this studi was to identify or find out how the influence of money politics on people’s choices in the 2017 Pilkades and identify or find out what faktors influence people’s choices in the 2017 Pilkades with the existence of money politics. The type of date used in this study is quantitative research. The location of this research is in the village of Teluk Limau, Gelumbang district, Muara Enim regency, south Sumatra province. And purely this research is the local community. To obtain date obtained numbered 1382 according to the permanent voter of samples was 93 respondents. To collecy date obtained is descriptive statiscal analyis. Theory in this study there are two theories used, namely the theory of Patronase and Klientelisme. There are five kinds of Patronase theory namely, Vote Buying, Individual Gifs, Services and Activities, Club Goods, Pork Barrel Projects. Whereas Klientelisme theories are of three kinds, namely the successs team, the social networking engine and political parties. In this study it was elections is very big influence on people’s voting behavior. In the 2017 Pilkades, the people of the village of Teluk Limau on average most of their voting behavior changes when they receive money politics. The faktors that influence the voting behavior of the Teluk Limau village in the 2017 elections are that people the and to choose the reasons because of economic faktors that have changed their choices after receiving money politics.